Antifungal activity of archidendron pauciflorum / Agnes Sameh - Sameh, Agnes (2017)
A research was conducted on Archidendron pauciflorum that was obtained from agro market Kuala Pilah, Negeri Sembilan by analyzing the antifungal activity of this plant extract using disc diffusion, minimum inhibition concentration and time kill study method against Candida albicans and Aspergillus spp.. For the disc diffusion, between the seeds extract and pods extract, seeds extract showing the biggest zone of inhibition of 25 mm against Candida albicans and 20 mm against Aspergillus spp. at 100 mg/mL and the smallest zone obtained from pods extract against Candida albicans and Aspergillus spp., 20 mm and 17 mm respectively for 100 mg/mL concentration. Seeds extract show remarkable antifungal activity than pods extract. Minimum inhibition concentration (MIC) was at 10 mg/mL concentration of seeds extract showing least turbidity. As for time kill study, the seeds extract actively killed the fungi at 8 hours. The results obtained provide evidence that Archidendron pauciflorum can be exploited more on its antifungal potential as a source of antifungal drug to be used in medicinal field in the future. Beside that its also can be processed as healthy food snack.